1989
DOI: 10.1055/s-2007-1001146
|View full text |Cite
|
Sign up to set email alerts
|

Isolierter Vitamin-E-Mangel

Abstract: Since the detection of vitamin E in 1922, nearly 50 years passed until the recognition that there is a pathogenic vitamin E deficiency in humans. Such a deficiency can be found mostly in a disturbed resorption or transport of the vitamin (mucoviscidosis, chronic cholestasis, abetalipoproteinaemia) and leads typically to a progredient spinocerebellar ataxia in combination with a polyneuropathy. Substitution of the vitamin may hinder a further progression or even lead to an amelioration of the symptoms. Prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Families 3 and 4 (referred by M. Ben Hamida) and 9 and 17 (referred by A. Benomar) belong to large series of Tunisian and Moroccan families, respectively, and are not part of this study. Clinical descriptions were reported elsewhere for families 13 (Burck et al 1981;Kohlschü tter et al 1988), 18 (Laplante et al 1984), 14 (Sokol et al 1988), 16 (Trabert et al 1989), 1 and 2 (Ben Hamida et al 1993b), 8 (Amiel et al 1995, and 28 (Martinello et al, in press), and mutation was reported for 10 families (Ouahchi et al 1995). In addition to the 27 families analyzed here, molecular and clinical data from 6 families were compiled from the literature (Gotoda et al 1995;Hentati et al 1996;Yokota et al 1996Yokota et al , 1997.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Families 3 and 4 (referred by M. Ben Hamida) and 9 and 17 (referred by A. Benomar) belong to large series of Tunisian and Moroccan families, respectively, and are not part of this study. Clinical descriptions were reported elsewhere for families 13 (Burck et al 1981;Kohlschü tter et al 1988), 18 (Laplante et al 1984), 14 (Sokol et al 1988), 16 (Trabert et al 1989), 1 and 2 (Ben Hamida et al 1993b), 8 (Amiel et al 1995, and 28 (Martinello et al, in press), and mutation was reported for 10 families (Ouahchi et al 1995). In addition to the 27 families analyzed here, molecular and clinical data from 6 families were compiled from the literature (Gotoda et al 1995;Hentati et al 1996;Yokota et al 1996Yokota et al , 1997.…”
Section: Subjectsmentioning
confidence: 99%
“…In normal individuals, the latter function accounts for the efficient recycling of plasma vitamin E ( pools/d) that otherwise is 1.4 ‫ע‬ 0.6 rapidly eliminated (Traber et al 1994). FIVE has been described in rare cases, studied during the period 1981-89 (Burck et al 1981;Laplante et al 1984;Harding et al 1985;Krendel et al 1987;Stumpf et al 1987;Yokota et al 1987;Kohlschü tter et al 1988;Sokol et al 1988;Trabert et al 1989). The description, reported in 1993, of eight affected individuals from two large Tunisian pedigrees (Ben Hamida et al 1993b) initiated the identification of many other patients from North Africa, where this condition appears to be much more frequent.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising, therefore, that long-term, severe vitamin E deficiency in our patients caused RP. Seventeen ataxia [5,6,[29][30][31][32][33][34][35][36][37][38][39]. They are sporadic or with family histories suggesting autosomal recessive inheritance.…”
Section: Long-term Vitamin E Deficiency In Animal Experimentsmentioning
confidence: 99%